Efficacy of a Self-Monitoring Tool for Improving the Quality of the Language Environment in the Preschool Classroom. Issue 1 (2nd January 2018) - Strasser, Katherine; Mendive, Susana; Vergara, Daniela; Darricades, Michelle
ABSTRACT: Research Findings : This study evaluated the impact of a self-monitoring intervention on preschool teachers' use of language and on children's language growth. Nineteen classrooms from Santiago de Chile participated (10 intervention, 9 control). Twice a week, intervention teachers filled out a checklist to monitor the language stimulation they offered children. Research personnel used the checklists to elaborate a monthly summary of the language opportunities offered to each child in that month and discussed this information with teachers. Results revealed a significant advantage for intervention teachers in frequency of book readings and word discussions but not on children's language growth. Dosage analyses showed that children identified by the self-monitoring device as receiving more language-learning opportunities improved significantly more from beginning to end of the school year in receptive vocabulary. Practice or Policy: Contextual barriers such as large numbers of children and unawareness of the impact of some language interactions can prevent teachers from engaging in important practices. Reminding teachers of the importance of those practices and helping them monitor their frequency may be a low-cost way of improving language opportunities for children in contexts where more intensive professional development is not possible.